Analysis Of Tenurial Conflict In Production Forest Management Unit (Pfmu) Model Poigar - Arif Irawan; Kristian Mairi; Sulistya Ekawati (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2016)
This Research aims to determine (1) History, actors and the causes of conflict in terms of the social aspect of economic, cultural and institutional happened in PFMU Model Poigar (2) Recommendations settlement to parse tenurial conflicts PFMU Model Poigar. Data analysis method used is a qualitative approach. The results showed that land claims by communities began of forest utilization activities to meet basic needs. Tenurial conflicts PFMU Model Poigar is a structural conflict. Some of the main actors should receive priority attention is the processing community land in the area and local employers. Some of the basic causes of conflict tenurial PFMU Model Poigar is a lack of understanding about the existence of related parties PFMU Model Poigar, the dualism of authority, lack of community empowerment, and law enforcement is still weak.Based on consideration of the history, the actors involved and the cause of the conflict, then some of the recommendation of this study is the institutional strengthening KPHP Poigar model, the development of that partnership, and law enforcement.